Key stakeholders' perceptions about school improvement strategies in UAE. (July 2019) - Al Ahbabi, Nafla Mahdi
This article reports on findings related to possible strategies of improving school effectiveness in Abu Dhabi from the perspectives of their stakeholders' perceptions, namely, principals, teachers, students, and parents. This study considered 18 strategies of meaningful school improvement (SI) to help align Abu Dhabi schools to international standards by assessing their policies, management, and performance as well as the roles played by each of the four groups of stakeholders. The close examination of these stakeholders' perceptions about change and improvement made it possible to identify five paramount strategies that may contribute to improving schools within the UAE secondary education system and perhaps leading toward more significant reform alignment. These are a participative reflective leadership, a common ambitious vision, a healthy learning environment, high expectations for success, and differentiated instructional strategies. The data indicated that schools could not be improved unless all the school parties are jointly involved as catalysts for change in forging the school's vision, environment, and prospects for success. The data were taken from research conducted in the Emirate of Abu Dhabi, the capital of the United Arab Emirates.